Recovery measures in star- rated hotels in Nairobi post-covid -19 pandemic - IMBIAKA, BERNICE (Strathmore University, 2021)
Since March 11, 2020, the World Health Organization (WHO) established a global pandemic status for 2019 coronavirus disease (COVID-19). Global pandemic status means that the disease is throughout the world; the entire world population wherever their country is, can be potentially be infected. This study aims to examine the recovery measures in star-rated hotels in Nairobi post-COVID-19 Pandemic.
The purpose of this study is to examine the recovery measures in star-rated hotels in Nairobi post-COVID-19 Pandemic. I will also examine how the post-COVID-19 era will be for the tourism and Hospitality industries post-recovery period. There will be an uneven recovery as some markets will be aligned with early phases of restarting tourism (Hall et al., 2020) In April 2020, the Organisation for Economic Cooperation and Development (OECD) (2020) estimated that the decline in international tourism in 2020 could be between 45% and 70%, depending on when recovery begins to take place and warned that the general economic decline due to the COVID-19 crisis will also delay recovery within the tourism industry (Jones & Comfort, 2020) .